KERATUAN ADAT MENANGSI DI LAMPUNG SELATAN - Herdius mafilindo; Muhammad Basri; Suparman Arif (University of Lampung, 2021)
Abstract: Menangsi Customary Association in South Lampung. The research objective was to see the history of the Menangsi Customary Association in South Lampung. The method used is historical research methods. Based on research results, the establishment of Keratuan Menangsi began with the collapse of Keratuan Balaw in the middle of the XVI century. Because of this collapse, according to several records, evidence, and the existing legacy of the